2018
DOI: 10.1039/c8dt01194j
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for the synthesis of VN@C and VC@C core–shell composites with hierarchically porous structures and large specific surface areas for high performance symmetric supercapacitors

Abstract: A novel strategy for the fabrication of vanadium nitride (VN) and vanadium carbide (VC) encapsulated into amorphous carbon nanotube core-shell structured composites (denoted as VN@C and VC@C) was developed by the thermal treatment with H2V3O8@C core-shell composites under N2 and Ar atmospheres, respectively. The as-prepared VN@C and VC@C were comprised of core-shell structures with cores of crystalline VN particles and particles and shells of amorphous carbon nanotubes. There are some O elements remaining both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…In recent years, research work has found that transition-metal nitrides (TMNs) exhibit the outstanding performance. Vanadium nitride (VN), as a typical TMN, possesses distinctive physical/chemical properties, such as high electrical conductivity, high melting points, and excellent corrosion resistance, which is a potential candidate catalyst for ORR. Zhao et al prepared well-defined VN hollow spheres assembled from the porous nanosheets via a template-assisted strategy, which was applied in lithium storage and ORR . Huang et al reported that a VN nanoparticle as an ORR catalyst was synthesized by a simple hydrothermal method; however, the ORR activity still needed to be enhanced …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research work has found that transition-metal nitrides (TMNs) exhibit the outstanding performance. Vanadium nitride (VN), as a typical TMN, possesses distinctive physical/chemical properties, such as high electrical conductivity, high melting points, and excellent corrosion resistance, which is a potential candidate catalyst for ORR. Zhao et al prepared well-defined VN hollow spheres assembled from the porous nanosheets via a template-assisted strategy, which was applied in lithium storage and ORR . Huang et al reported that a VN nanoparticle as an ORR catalyst was synthesized by a simple hydrothermal method; however, the ORR activity still needed to be enhanced …”
Section: Introductionmentioning
confidence: 99%
“…Generally, to enhance the storage performance of VN, strategies such as nanostructuring [ 18 , 19 , 20 , 21 ] and hybridization [ 22 , 23 , 24 ] have been employed. The hybridization approach involves carbon-based hybrids [ 21 , 25 , 26 ] and carbon-free hybrids [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, to enhance the storage performance of VN, strategies such as nanostructuring [ 18 , 19 , 20 , 21 ] and hybridization [ 22 , 23 , 24 ] have been employed. The hybridization approach involves carbon-based hybrids [ 21 , 25 , 26 ] and carbon-free hybrids [ 27 , 28 ]. For the VN-carbon-based hybrids electrodes, tremendous advancement has been realized [ 29 , 30 , 31 ], whereas carbon-free VN-based hybrids are still at their starting stage [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, low-lost vanadium-based oxides have been considered as a class of outstanding pseudocapacitive materials and are widely used in energy storage in view of the rich valence states of vanadium. [30][31][32] Thus, the V 2 O 3 /C precursor is used as a positive electrode (0-0.5 V) for assembling an ASC device with VN/NCS as the negative electrode (À1.1 to 0 V). The favorable electrochemical performance of the (+) V 2 O 3 /C//VN/NCS (À) ASC device is presented.…”
Section: Introductionmentioning
confidence: 99%